PENYULUHAN BAHAYA NARKOBA OLEH UKM GRANAT UBHARA JAYA DALAM MEMBANGUN DAN MENINGKATKAN KUALITAS GENERASI MUDA ANTI NARKOTIKA - Syahrir Kuba; Octo Iskandar; Mohamad Dimyati Hadi Saputra (Abdi Bhara, 2023)
Narcotics is an abbreviation of Narcotics,Psychotropics and other Addictive Substances which are enemiesof the nation and state. In Indonesia, in particular, narcoticsabuse is still massive, especially among the younger generation.This can of course happen due to a lack of understanding aboutthe dangers and impacts of drugs themselves. UKM GranatBhayangkara Jakarta Raya University, as an Anti-NarcoticsAbuse Movement, often holds community service activities,especially in educating people about the dangers of drugs. Thistime the education activity on the dangers of drugs was carriedout at SMAN 8 Kota Bekasi. The service methods used are survey,counseling and question and answer methods. Based on thedescription and results of the discussion of this service activity, itcan be concluded that drugs are the nation's enemy and oftentarget the younger generation. An understanding of narcoticsand other addictive substances has a positive impact on studentsat SMAN 8 Kota Bekasi in protecting themselves and theenvironment. The response from students at SMAN 8 Kota Bekasiwas very good as seen from the high enthusiasm for askingquestions during the question and answer session. As well as theneed for follow-up in providing a more detailed understandingregarding the role of the younger generation in fighting narcoticsfor themselves and the environment.